Green Extraction of Microcrystalline Cellulose from Cabbage Waste (Brassica Oleracea L.) via Steam Explosion Under Pressurized and Non-Pressurized Nitrogen (N2) - Syafira, Nesha Permata; Airlangga, Bramantyo; Sumarno (Eksergi, 2025)
Agricultural residues such as cabbage waste (Brassica oleracea L.) are rich in cellulose and offer promising potential for sustainable microcrystalline cellulose (MCC) production. This study aims to extract and characterize MCC from cabbage waste using an environmentally friendly approach that combines high-speed blending, low-concentration oxalic acid hydrolysis (0–2% w/v), and steam explosion at 130 °C for 15 minutes, under both pressurized and non-pressurized nitrogen (N₂) atmospheres. The application of pressurized N₂ significantly improved delignification efficiency and preserved cellulose crystallinity. The optimal treatment (2% oxalic acid with N₂) yielded a cellulose content of 79.18%, with hemicellulose and lignin contents reduced to 15.28% and 0.10%, respectively. FTIR analysis confirmed the effective removal of non-cellulosic components, while XRD analysis revealed a crystallinity index 66%, which is high compared to typical MCC values from other biowastes (~50–60%). SEM revealed clean and well-dispersed fiber morphology. These results indicate that oxalic acid combined with N₂-assisted steam explosion is an effective and eco-friendly method for producing MCC. This approach minimizes chemical use and oxidation, making it suitable for pharmaceutical excipients, biodegradable composites, and other green material applications. Overall, the process aligns with circular economy principles and contributes to the Sustainable Development Goals (SDGs).